Foreign Experience of State Regulation of Innovative Products and Innovations in Supply Chain Management in the Modern Economy - Ildar M.Ablaev (International Journal of Supply Chain Management, 2019)
State innovation policy is designed to cover all aspects of science, research and technology: legal, economic, organizational and managerial. The state innovation policy is a system which consists of three levels: national, regional and local. The levels complement each other, despite the fact that the significance and scope of the policies implemented on each of them are different. Through this research, we explore innovations in supply chain management (SCM), in which a manufacturer coordinates and supports the innovations of a supplier. We also analyze the role of innovation policy in the region, which is considered to be leading in the policy of the â€œnew feudalismâ€ of the United States and in the Lisbon Strategy for Growth. The state innovation policy aims to mobilize and activate internal reserves of the country's innovative potential, in particular, innovations in logistics, human resource and scientific and technical potential of the region.